A novel hybrid equivalent circuit model for lithium-ion battery considering nonlinear capacity effects. (September 2021) - Chen, Dongdong; Xiao, Long; Yan, Wenduan; Guo, Yinbiao
Abstract: In this paper, a novel hybrid equivalent circuit model for lithium-ion battery. The proposed equivalent circuit model of lithium-ion battery is based on Thevenin equivalent circuit model, and a state-of-charge (SOC) part is added into the model to improve the model performance. In the proposed model, the battery capacity is divided into available capacity and unavailable capacity, which can well reflect the rated capacity effect when the battery is working, the recovery effect when the battery is not working and the self-discharge effect at all times. At the same time, a new definition of the SOC is given. The SOC value of the battery is estimated in real time through the model of the charged state part, and the one-to-one correspondence between SOC and open circuit voltage is established. Besides, the second-order polarized RC network in Thevenin model is improved to the third-order RC network, and the third-order RC network is endowed with practical physical significance, to reflect the polarization effect of the battery more accurately. Finally, Simulink simulation and experimental results have verified the correctness of the proposed model.